Anatomy of the Mediterranean Diet and Mortality Among Older Women with Frailty. Issue 3 (2nd October 2018) - Zaslavsky, Oleg; Zelber-Sagi, Shira; Shikany, James M.; Orchard, Tonya; Wallace, Robert; Snetselaar, Linda; Tinker, Lesley
Abstract: We examined individual components of the Mediterranean Diet (Med) and evaluated their relative contribution to mortality rates in older women with frailty. A sample ( N = 10, 431) included Women's Health Initiative Observational Study participants aged 65-84 y with complete frailty diagnostic criteria and dietary data. Frailty was assessed with modified Fried's criteria, and dietary data were collected through food frequency questionnaire. Over a mean follow-up of 12.4 y (range 3–21.0), 3, 259 (31.2%) deaths occurred. Crude death rates demonstrated a decrease in mortality with higher intake of individual Med components. However, in the mutually adjusted models, most Med components on their own were not significantly associated with mortality. Exceptions were vegetables, nuts, and whole grains. A higher intake of vegetables, nuts, and whole grains were associated with a significantly decreased hazard of mortality, by 9% ( P = 0.02), 13% ( P < 0.001), and 17% ( P < 0.001), respectively. The relative contribution of these components to diet mortality associations were 21%, 42%, and 57% for vegetables, nuts, and whole grains, respectively. Subgroup analyses by chronic morbidity, smoking status, or excluding women with early death did not substantially change these results.